The impact of food price shocks in Uganda: First-order versus long-run effects - Van Campenhout, Bjorn; Pauw, Karl; Minot, Nicholas (International Food Policy Research Institute, 2013)
We look at the immediate effects of these shocks faced by households in Uganda on their poverty and well-being. In addition, we look at the economywide impact in the long run when all markets have settled at a new equilibrium. We find that in the short run, poverty has increased substantially. However, in the longer run, we find welfare levels of rural farm households in particular to rise sharply, primarily as a result of increased returns to farm labor and agricultural land coupled with improved market prices for output sold.